Rock glaciers in central Patagonia. Issue 1 (2nd January 2019) - Selley, Heather; Harrison, Stephan; Glasser, Neil; Wündrich, Olaf; Colson, Daniel; Hubbard, Alun
ABSTRACT: Active rock glaciers are ice and debris-cored landforms common in cold arid mountains. They have not been widely described in the Patagonian Andes of southern South America and here we provide the first rock glacier inventory for the Jeinimeni region to the east of the contemporary North Patagonian Icefield. Detailed analysis of available satellite imagery and fieldwork demonstrates the presence of 89 rock glaciers across the study region, covering a total of 14.18 km 2 . Elevation is the primary control on rock glacier distribution with 89% existing between 1600 and 1900 m.a.s.l. Aspect also plays a significant role on rock glacier formation with 80% preferentially developed on southerly slopes receiving lower solar insolation.